2019
DOI: 10.1088/1742-6596/1318/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Building children’s learning motivation through positive reinforcement in science and math classroom

Abstract: This research is based on how the teacher builds a learning motivation of 5-6 years old children. In the classroom, sometimes children’s motivation decrease, there is one way to build learning motivation on children, it is called positive reinforcement. This research aims to determine the learning motivation of 5-6 years old children by giving positive reinforcement in the math and science subject. The method of this research was qualitative descriptive with the sample was six students of B2 class around 5-6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Motivation to learn is the overall driving force within students that causes learning activities, which ensures the continuity of learning activities and provides direction for learning activities to achieve the goals desired by the learning subject [76,77]. Motivation is a power or strength that arises from within students to provide readiness to achieve predetermined goals.…”
Section: -5-motivation To Learnmentioning
confidence: 99%
“…Motivation to learn is the overall driving force within students that causes learning activities, which ensures the continuity of learning activities and provides direction for learning activities to achieve the goals desired by the learning subject [76,77]. Motivation is a power or strength that arises from within students to provide readiness to achieve predetermined goals.…”
Section: -5-motivation To Learnmentioning
confidence: 99%
“…Positive reinforcement is teachers' responses to students' positive behaviors so that students can increase their frequency to perform them. Some earlier studies showed the effectiveness of the application of positive reinforcement in boosting students' positive behavior in the learning process (Sigler & Aamidor, 2005;Uddin et al, 2017;Hardy & McLeod, 2020;Sumiati et al, 2019). The positive reinforcement can be applied in various forms like giving a present, award, or oral and written compliments.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention Results [45] This research is based on how the teacher builds learning motivation in 5-6-year-old children Social reinforcer -Encourages pupils to keep up their good behavior.…”
Section: Study Objectivementioning
confidence: 99%
“…Kinyanjui, A. et al [56] conducted a study involving 4-and 5-year-old children to enhance their motor learning activities, and they concluded that reinforcement and its timing are important factors in the development of operant behavior and learning. When the use of a continuous reinforcement schedule raises the response rate, the use of a discontinuous reinforcement schedule may cause the response rate to decrease, thereby leading to the termination of such a reaction or behavior in young learners [45,46].…”
mentioning
confidence: 99%